Analisis Kepuasan Pengguna Google Classroom Menggunakan Pieces Framework (Studi Kasus: Program Studi Sistem Informasi Uin Jakarta) - Yolanda Rizkyta Sari; Evy Nurmiati (Universitas Islam Sumatera Utara, 2021)
The use of online learning media is currently widely used by all students and students in Indonesia, this is due to the covid-19 pandemic that requires students to do online learning. Media Knowledge Management System (KMS) is a must in every online learning. Online learning media is very much an option, one of which is google classroom. Google classroom is one of the most popular and used learning media. This study aims to analyze and know the level of google classroom user satisfaction by students of UIN Syarif Hidayatullah Jakarta Information System in the learning process. Satisfaction of the use of an application was formed because of the service provided by a system that can be customized to the user's wishes. This research uses PIECES framework method consisting of Performance, Informations and data, Economics, Control and security, Efficiency and Service. The result of this study obtained the average value of each domain, namely performance domain gets a value of 4,188 (Satisfied), Informations and data get a value of 4,194 (Satisfied), Economics gets a value of 4.013 (Satisfied), Control and security gets a value of 4.074 (Satisfied), Efficiency gets a value of 4,457 (Very Satisfied) and Service gets a value of 4.3 (Very Satisfied). As for the total average satisfaction level of all domains, it gets a score of 4,204 (Very Satisfied).